Smallholders Perception on Mutation Breeding's Muna Teak Demonstration Plot in Cariu Private Forest - Desmiwati Desmiwati; Naning Yuniarti; Yulianti Bramasto; Muhammad Zanzibar; Ratna Uli Damayanti Sianturi; NFN Megawati (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2021)
Teak wood is the superior wood for carpentry, and the need for carpentry continues to increase in Indonesia. It has prompted various efforts to increase teak production, both in state forests and non-state forests. One of the efforts to increase teak production is using advanced science and technology, superior teak seedlings from mutation breeding. This study aims to describe smallholder's perception of the demonstration plot of Muna Teak from mutation breeding in the Cariu Private Forest, Bogor Regency. The research used two methods: Focused Group Discussion and semi-structured interviews by questionnaires. For the analysis, the study used the perceptual process framework) to explore the data from the two methods and present it descriptively. The result shows that smallholders had a good perception toward the mutation breeding Muna Teak demonstration plot. Smallholders can carry out intercropping (agroforestry) activities in the demonstration plot and increase their knowledge of forestry plant cultivation, especially teak. The activity provides an opportunity for smallholders to improve their welfare.